THE ART OF ULUGBEK KHAMDAM’S NOVEL “BALANCE” (The Conference Hub, 2025)
This article presents analyses and comments on the participation of various characters and people of different professions in the life paths of Ulugbek Hamdam’s novel “Balance”, their aspirations to continue life, and their attempts to maintain their balance even after the trials they face.